Exploring the Role of the Music Teacher from the Perspectives of Parents and Teachers in West Malaysia - Ang, Kathryn; Panebianco, Clorinda; Odendaal, Albi (Malaysian Journal of Music, 2019)
It is important for music teachers to reflect on the influence of their role during lessons. However, the roles of teachers, and expectations from both teachers and parents are often unclear, resulting in role confusion on both sides. The purpose of this collective case study is to describe and understand the expectations of both parents and teachers of the teacher’s role in group music lessons for pre-school children in the Klang Valley1of West Malaysia. Two semi-structured interviews were conducted with ten parents and three teachers of three group music classes for pre-school children. This study situates role theory as a conceptual framework to explore the perspectives of parents and teachers on the expected roles of teachers in group music lessons. Five broad categories of themes emerged, namely parent-teacher perspectives on teachers’ roles asmulti-faceted professionals, authorities on music, entrepreneurs, mentors and communicators. A novel finding showed that teachers in West Malaysia play the role of entrepreneurs. Teachers are expected to be customer service providers, even babysitters, and are also expected to be generous with their time, which influences their entrepreneurship. The paper argues that role theory is a helpful tool in order to help teachers to understand how their roles play out in West Malaysia and how an understanding of their roles can help teachers to clarify the many expectations placed on them.